Livestock-associated methicillin-resistant Staphylococcus aureus (clonal complex 398) causing bacteremia and epidural abscess. (April 2019) - Murra, M.; Mortensen, K.L.; Wang, M.
Highlights: Concerns about MRSA CC398 being capable of causing invasive infections in the general population. MRSA CC398 may have a greater pathogenic potential that previously assumed. MRSA CC398 is not limited to at-risk people due to livestock-exposure or predisposing disease. Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) clonal complex (CC) 398 has spread from pigs to humans, but rarely from person to person. This strain of MRSA has been considered less virulent than others. Livestock-associated MRSA CC398 (LA-MRSA CC398) is particularly known to colonize pig farmers. Recent studies have shown an increasing number of people colonized with LA-MRSA CC398 and invasive infections caused by LA-MRSA CC398. The case of a previously healthy, 61-year-old woman admitted to a Danish regional hospital is reported here. She presented with fever, severe back pain, and bilateral hyperreflexia of patellar and Achilles reflexes. Blood tests revealed leukocytosis and elevated C-reactive protein. Empiric antimicrobial therapy with intravenous piperacillin–tazobactam was initiated, but blood cultures grew MRSA and antimicrobial therapy was changed to intravenous vancomycin. Whole-genome sequencing showed that the MRSA strain belonged to LA-MRSA CC398 spa type t011 and was Panton–Valentine leukocidin-negative. Magnetic resonance imaging revealed an epidural abscess at the level of L1–L4. Surgery was performed and pus from the abscess grew MRSA. The duration of antimicrobial therapy was 12 weeks. This case report describes bacteremia with LA-MRSA CC398 in a previously healthy patient without exposure to livestock or previous admission to a hospital. This highlights the risk of person-to-person transmission of LA-MRSA CC398 and brings into question whether LA-MRSA CC398 may have a greater pathogenic potential than previously assumed.